Size and power properties of structural break unit root tests - Narayan, Paresh Kumar; Popp, Stephan (Applied economics, 2013)
In this article, we compare the small sample size and power properties of a newly developed endogenous structural break unit root test of Narayan and Popp (NP, 2010 ) with the existing two break unit root tests, namely the Lumsdaine and Papell (LP, 1997 ) and the Lee and Strazicich (LS, 2003 ) tests. In contrast to the widely used LP and LS tests, the NP test chooses the break date by maximizing the significance of the break dummy coefficient. Using Monte Carlo simulations, we show that the NP test has better size and high power, and identifies the structural breaks accurately. Power and size comparisons of the NP test with the LP and LS tests reveal that the NP test is significantly superior.